Efektivitas Pengelolaan Keuangan Desa Di Desa Sijungkang Kecamatan Angkola Timur Kabupaten Tapanuli Selatan - Amelia, Iska (Fakultas Dakwah dan Ilmu Komunikasi, 2018)
The problem in this study is that the development in Sijungkang Village is not in accordance with village funds given to the village government, where the existing development in the village is of poor quality such as footpaths and water ropes. With village funds, the amount of development in the village should be of high quality and durable, but the reality of the village development is that there are several buildings that have been damaged for a year, such as footpaths and water ropes. The formulation of the problem in this study is,